2019
DOI: 10.1186/s12983-019-0312-2
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic reprogramming involving glycolysis in the hibernating brown bear skeletal muscle

Abstract: Background In mammals, the hibernating state is characterized by biochemical adjustments, which include metabolic rate depression and a shift in the primary fuel oxidized from carbohydrates to lipids. A number of studies of hibernating species report an upregulation of the levels and/or activity of lipid oxidizing enzymes in muscles during torpor, with a concomitant downregulation for glycolytic enzymes. However, other studies provide contrasting data about the regulation of fuel utilization in sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(83 citation statements)
references
References 78 publications
(117 reference statements)
10
69
0
Order By: Relevance
“…Accordingly, we found that the concentration of total circulating fatty acids was elevated in hibernating bears, a nding in line with previous studies [5,44]. Considering both the amount and relative proportions of circulating lipids, our results are consistent with changes in serum and plasma lipid pro les during hibernation that have been previously published [5,9,10], notably an enrichment in DHA C22:6 n-3 and depletions in ALA C18:3 n-3 and EPA C20:5 n-3, during winter compared to summer. Whether the depletion in the ALA and EPA precursor species could be directly linked to the observed DHA increase remains to be elucidated.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Accordingly, we found that the concentration of total circulating fatty acids was elevated in hibernating bears, a nding in line with previous studies [5,44]. Considering both the amount and relative proportions of circulating lipids, our results are consistent with changes in serum and plasma lipid pro les during hibernation that have been previously published [5,9,10], notably an enrichment in DHA C22:6 n-3 and depletions in ALA C18:3 n-3 and EPA C20:5 n-3, during winter compared to summer. Whether the depletion in the ALA and EPA precursor species could be directly linked to the observed DHA increase remains to be elucidated.…”
Section: Discussionsupporting
confidence: 93%
“…DHA appears to prevent muscle atrophy in fasting mice, and increases muscle glycogen stores [45]. Strikingly, in parallel to DHA serum enrichment, hibernating bears have more than a 3-fold higher glycogen muscle content compared to summer-active animals [10]. In addition to its anti-in ammatory effects, DHA is also known to exert a positive effect on protein balance by decreasing expression of factors involved in protein breakdown [46] and enhancing protein synthesis, notably by promoting mammalian Target Of Rapamycin (mTOR) activation [47].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations